Combination Of Cymbopogon Citratus and Citrus Aurantifolia Aromatherapy as a Complementary Therapy to Reduce Maternal Anxiety During Childbirth - Rahmawani Fauza; Helena Fransysca (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2025)
Anxiety during labor is a common psychological condition experienced by pregnant women, particularly primigravida mothers, and may negatively affect the labor process. Poorly managed anxiety can increase pain perception, inhibit uterine contractions, prolong labor, and adversely impact maternal and fetal well-being. Pharmacological management of anxiety has limitations due to potential side effects; therefore, safe and effective complementary therapies are needed. Aromatherapy has been widely used in midwifery care due to its relaxing and anxiolytic effects. Cymbopogon citratus and Citrus aurantifolia essential oils contain bioactive compounds that provide calming, refreshing, and mood-enhancing effects, and their combined use is expected to produce a synergistic effect in reducing anxiety during labor. This study aims to examine the effectiveness of a combination of Cymbopogon citratus and Citrus aurantifolia aromatherapy as a complementary therapy in reducing maternal anxiety during labor. This study employs a quasi-experimental design with a pretest–posttest control group approach. The subjects are laboring mothers who meet the inclusion criteria. Data are analyzed to determine differences in anxiety levels within and between groups. The combination of Cymbopogon citratus and Citrus aurantifolia aromatherapy is expected to significantly reduce anxiety levels among laboring mothers compared to standard care alone.: The use of combined Cymbopogon citratus and Citrus aurantifolia aromatherapy has the potential to serve as a safe, practical, and effective non-pharmacological intervention to reduce maternal anxiety during labor. This therapy may support holistic midwifery care by improving maternal comfort and psychological well-being during childbirth.